Sexism in Indonesia’s Tenth Grade EFL Companion Textbook - Ratna Afina Firstyani; Yuni Utami Asih; Bibit Suhatmady (Yayasan Visi Intan Permata, 2022)
The present study investigates the kind of sexism reflected in the companion textbook used in Senior High School: the frequency of female and male occurrences, the female and male titles, the graphic depiction of females and men, the masculine pronoun tendency, activities, and social-domestic roles throughout the description phase. It also examines how occupational gender stereotypes are portrayed in textbooks. This analysis was conducted by applying Fairclough's three-dimensional analysis and Halliday’s Systemic Functional Linguistics. Finally, this research indicated that textbooks had a sexist mindset characterized by gender marginalization, gender subordination, gender stereotypes, cultural sexism, and sex-based work segregation. The textbooks were biased toward females by depicting females less frequently than males in pictorial representation (58.48 vs 33.97 percent); the titles Mr. and Mrs. were used inconsistently, and there were 12 instances of masculine pronoun tendency, representation of activities, and social-domestic roles that perpetuate female subordination. The research also found that there were considerably fewer images of women than males in the public domain, suggesting that women in traditional gender roles such as cooking and caring for children were far more prevalent. In terms of occupational gender stereotypes, the survey indicated that male jobs were more prevalent and diversified than female ones. In terms of social duties, men were found to have a greater selection of occupations than females.